PELATIHAN PEMANFAATAN BENDA-BENDA SEKITAR DAN PERMAINAN UNTUK MEDIA PEMBELAJARAN MIPA DAN IPS DI SD SANJAYA TRITIS PAKEM - Ignatia Esti Sumarah; Kintan Limiansih; Christiyanti Aprinastuti; Andreas Erwin Prasetya (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2018)
The purpose of this training was to facilitate elementary school teachers in Sanjaya Elementary School Tritis, Pakem so that they were able to provide learning media for Natural and Social Sciences. The learning media was a set of equipment that could be used as learning media to help teachers deliver lessons to the students so that students were motivated to learn. Media that could be used should be helpful for the students to understand the concept of learning, be suitable with the characteristics of the students, and facilitate the students to obtain the learning objectives, as well as appropriate with the learning condition, facilities and time availability. This training was directed in such a way that the teachers in that school became creative in utilizing objects around them to teach Natural and Social Sciences. Games were also used to teach Mathematics.